Synthesis And Characterization Of Carbon Coated And Nitrogen Doped Tio2 For Enhanced Photocatalytic Degradation Of Organic Pollutants Under Uv-Vis And Visible Light Irradiation - Ismail, Wan Izhan Nawawi Wan (2013)
A commercially available and relatively cheap TiO2 (99% anatase) and TiO2-P25 (80% anatase and 20% rutile) were modified to produce carbon (C) and nitrogen (N) incorporated TiO2 to improve its photoactivity under UV-Vis and visible light regions. Both the TiO2 and TiO2-P25 were modified using natural polymers of ENR-50 and peat coagulant (peat) as carbon precursor while urea was used as N and C precursor. TiO2 modified with ENR-50 produced a C coated TiO2. The optimum condition for C coating was 1.0 g ENR-50 solution and 560 °C of calcination temperature to yield the optimum C coated sample containing 0.25 % C with a C layer thickness of 0.68 nm. By using Reactive Red 4 dye (RR4) as model pollutant, the photocatalytic degradation rate of the optimum C coated TiO2 was 3.7 and 5.5 times faster than that of the pristine TiO2 under 45 W fluorescent lamp and solar irradiations respectively. The C layer present in TiO2 was responsible for increasing its photoactivity by acting as an electron scavenger. However, no photocatalytic degradation was observed under visible light irradiation for all C coated TiO2 due to their bandgap energy (Eg) values higher than 3.0 eV.